Analysis of Increased Participation of Agriculture in the Brazilian GDP From 1960 to 2004 - Carlos Bacha; Ricardo Brugnaro (European Regional Science Association (ERSA), 2006)
According to international experience, the importance of agriculture in the gross domestic product (GDP) has a declining trend during the time. It has happening in all nations, including in Brazil from 1960 to 1993. However, starting in 1994 Brazil has experiencing an increasing in this variable, what has not being followed by most of the South American countries. This paper analyzes the factors that explain the increase of agriculture importance in the Brazilian gross domestic product during the last 11 years, comparing Brazilian experience with other South American and the most developed countries in the world. The methodology used is both organization of published dataset in graphs and tables as well as econometric analysis of these data. An accounting model is developed for explaining the main factors affecting the importance of agriculture in the GDP and an econometric model is adapted for estimating the accounting model. Using dataset from 1986 to 2004, our econometric findings suggest there is a structural change in the curve of agriculture share in the GDP, and the increase of agricultural production and productivity as well as the increase of (prices received/prices paid) ratio are the most important variables determining the increase of agriculture importance in the Brazilian GDP since 1994.
Keywords: 330